Studi Kepustakaan Penerapan Art Therapy dalam Bimbingan dan Konseling - Ichsana Nur Asyifa; Naharus Surur; Agus Tri Susilo (Jurnal Psikoedukasi dan Konseling)
Abstract: This study aims to examine the application of art therapy which includes goals, scope, techniques, procedures, and the effectiveness of its application in guidance and counseling. The method used in this research is a literature study to collect and integrate various information on the application of art therapy. The data sources used were 27 research articles on art therapy which were analyzed using content analysis techniques. Checks between libraries are carried out to ensure the validity of the data. The results of this study are: (1) The targets of the application of art therapy are school-age students who are classified as children and adolescents of male and female sexes. (2) The scope of application of art therapy is in the form of personal-social, academic, and career problems. (3) Techniques for applying art therapy include drawing, painting, coloring, collage, clay, altered books, or other creative activities related to art-making and combining them with techniques in other counseling approaches. (4) The procedure for applying art therapy consists of 3 main stages: preparation, making art, and closing. (5) The application of art therapy, namely art therapy, is practical for solving personal-social, academic, and career problems. This research is recommended to further researchers to be used as a reference for research in a broader setting.